2009
DOI: 10.1111/j.1365-2389.2009.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil phosphorus on particulate phosphorus in land runoff

Abstract: Accumulation of surplus phosphorus (P) in the soil and the resulting increased transport of P in land runoff contribute to freshwater eutrophication. The effects of increasing soil P (19-194 mg Olsen-P (OP) kg À1 ) on the concentrations of particulate P (PP), and sorption properties (Q max , k and EPCo) of suspended solids (SS) in overland flow from 15 unreplicated field plots established on a dispersive arable soil were measured over three monitoring periods under natural rainfall. Concentrations of PP in plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Especially in the manured plot, where P surplus was very high, soil and dispersed solids were similarly saturated, confirming that this soil has reached the maximum P sorption capacity to buffer further P addition and accounting for the higher soluble P content. Withers et al (2009), studying collected sediments from overfertilised soils, showed that the suspended solids were more saturated than the relative bulk soil on plots with Olsen P<100 mg kg −1 , whilst the inverse occurred in soils with higher Olsen P levels and the suspended solids changed from being a source to sink of P. Moreover, the finest particles detached were Cenriched and depleted in poorly crystallised Fe and Al oxides. Particle composition and P sorption may affect surface electrical charge and, hence, soil dispersibility (Celi and Barberis 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Especially in the manured plot, where P surplus was very high, soil and dispersed solids were similarly saturated, confirming that this soil has reached the maximum P sorption capacity to buffer further P addition and accounting for the higher soluble P content. Withers et al (2009), studying collected sediments from overfertilised soils, showed that the suspended solids were more saturated than the relative bulk soil on plots with Olsen P<100 mg kg −1 , whilst the inverse occurred in soils with higher Olsen P levels and the suspended solids changed from being a source to sink of P. Moreover, the finest particles detached were Cenriched and depleted in poorly crystallised Fe and Al oxides. Particle composition and P sorption may affect surface electrical charge and, hence, soil dispersibility (Celi and Barberis 2005).…”
Section: Discussionmentioning
confidence: 96%
“…For example, Dodd et al (2012) estimated it would take between 23 and 44 years to lower STP sufficiently to reach a solublereactive P (SRP) concentration of 0.02 mg L -1 in runoff from grazed grassland required for eutrophication control. Even longer timescales can be expected to reduce the P content of eroding soil particles due to their insensitivity to changes in STP in agricultural settings (Withers et al 2009). Lowering of STP and SRP release to runoff may also be more difficult to achieve in agricultural systems that rely on no-till, crop residue and cover crop management techniques that concentrate available soil P at the surface (Smith et al 2014).…”
Section: Environmental Benefits and Trade-offsmentioning
confidence: 99%
“…This occurs because of the combined effect of relatively low N:P ratios of biosolids (typically less than 1) with soil applications based entirely on N requirements by crops, which results in over-application of P relative to crop requirements. Surplus of phosphorus in soils receiving periodic applications of biosolids influences soil P dynamics and can enhance transport of P to water courses when the soil sorption capacity is exceeded (Smith et al 2006;Withers et al 2009). Therefore, understanding the availability of P from organic-based fertilizers applied to soil is an important agronomic and environmental consideration for nutrient management.…”
Section: L Antille Et Almentioning
confidence: 99%